High-performance room-temperature ammonia gas sensor based on molybdenum trioxide nanostructure / Chua Wen Hong - Chua , Wen Hong (2021)
In this research, h-MoO3 nanostructure were grown on tapered region of optical fiber glass via simple chemical bath deposition (CBD) to form a unique sensing element to detect ammonia (NH3) gas in room temperature. As NH3 gas sensor have been highly demanded due to its commonly utilization of NH3 gas in various industrial sectors and a highly toxic and corrosive agent that can cause threat human health and environment. Experiment parameter such as type of precursor used, precursor concentration, deposition time and annealing treatment was performed to fine-tuned the growth of h-MoO3 nanostructure and optimised the NH3 gas sensing performance. The structural, thermal and optical properties of the sample were studied by using field emission scanning electron microscope (FESEM), energy dispersive X-ray (EDS), selected area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR) and UV-Vis spectroscopy. The morphology of the deposited h-MoO3 is highly affected by the types of precursors used. As different precursor concentration and deposition time also affect the overall sensing performance. Overall, the annealing treatment improves the sensitivity, respond time and recovery time of the sensor towards NH3 gas. However, overheating the sample cause disruption towards gas adsorption due to its metastable characteristic. Among them, the sodium-based h-MoO3 nanorod sample annealed at 150oC shows a stable room-temperature respond of 0.05, 0.18, 0.22, 0.28 and 0.35 au, a fast respond time of 210 s towards 500 ppm of NH3 and good stability and repeatability. The optical NH3 gas sensing behaviour have a significant relationship with the interaction between the h-MoO3 nanostructure and the evanescent wave. The chemisorbed oxygen species and physisorbed NH3 alter the refractive index and its absorption coefficient on the MoO3 nanostructure which provide manipulation of optical signal as sensing mechanism. This work proved that a chemical bath deposition grown h-MoO3 nanostructure exhibits a promising optical sensing characteristic which shed a light for new emerging gas sensing technology.